The Role of Play Methods in Increasing Students' Courage in Doing Backward Rolls at SD Inpres Sambung Jawa I - Asyhari, Hasbi; Nurliani, Nurliani (SHOOTING: Journal of Sport, Health, and Education, 2024)
This study aims to improve the courage of fifth grade students in doing backward rolls in floor gymnastics through the application of interactive and fun learning methods. The method used is Classroom Action Research (CAR) consisting of two cycles. Initial data showed that only 24.2% of students achieved learning completion with a score above 75. After corrective actions in Cycle II, the percentage of students who achieved completion increased to 8.08%. These results indicate that the approach applied is effective in increasing student involvement and self-confidence. This study recommends the use of creative methods in gymnastics learning to achieve better results and meet student needs optimally.